Biomechanical effect of en-masse versus substep extraction space closure on posterior teeth using clear aligners: a finite element study - Jiang Yiru; Mei Li; Xu Li; Wang Jue; Feng Xiaoxia; Chen Xiaoyan (Australasian Orthodontic Journal)
To evaluate the biomechanical effects of en-masse versus substep extraction space closure on posterior teeth during clear aligner treatment and to provide guidelines for optimising anti-tipping designs.